The use of communication technologies to support teaching and learning practices in portuguese higher education - Ramos, Fernando
The use of Communication Technologies (CTs) to support teaching and learning in higher education (HE) has emerged as a research topic worldwide. At the University of Aveiro (Portugal) the TRACER project began researching in 2011 the use of CTs to support teaching and learning practices in Portuguese Public Higher Education Institutions (PPHEIs). Data was collected through two online surveys distributed at two different moments during the project’s life cycle. The first survey, answered by decision makers at the rectory level of the PPHEIs, focused on the institutional perspective of the support to the use of CT in their teaching and learning related activities. The second survey, answered by teachers from the same PPHEIs, focused on the perspective of the use of CT in their teaching practice. Results from the institutional perspective globally show that from the total of courses of all existing cycles in respondent Higher Education Institutions (HEIs), 5.9% are delivered entirely online and 4.2% in a blended modality, most of them at undergraduate and post-graduate (master) levels. Regarding the provision of online learning management systems to support teaching and learning, results showed that the open source platform Moodle is the most commonly adopted, in some HEI coexisting with other similar platforms. The analysis of the teachers and students usage of these online platforms shows higher level of use in institutions offering courses online or in blended formats. From the teachers’ perspective, global results show that interpersonal CTs and institutional learning management systems are the most used. Regarding pedagogical use, online platforms seem to be used mostly for dissemination purposes. Communication between teachers and students in class and extra-class (95,7%) scenarios and the possibility of making available diverse educational resources to students (93,5%) are recognized as positive issues. The volume of tasks demanded for integrating CTs in the educational process by teachers is perceived as the most negative aspect (44,3%). Main reasons for using CTs in the teaching process are student motivation for learning (77,8%) and innovation in teaching practices (74,6%). The main results of the project are consolidated in a web-based tool, U-‐TRACER, which provides support for the handling and deployment of information about the use of CTs through the extensive use of information visualization features that include specific filters such as: single HE institution selection or georeferenced filtering. Filtered results can be downloaded and shared in social networks. This paper provides an overview of the U-‐TRACER project, the methodology adopted for its development and inherent data collection activities, a brief outline of some results attained through the surveys applied and, towards the end, a brief presentation of the tool itself and some of the conclusions drawn from the project as a whole and some perspectives about its future and sustainability.